Severe chest pain after retention of wireless pH capsule - Duarte-Chang, Calixto (2023)
The wireless capsule to measure gastroesophageal reflux, also known as pH monitoring capsule, is a technique used in ambulatory reflux monitoring. This capsule is introduced through a guide into the esophagus and is placed using a suction system and anchored to the esophageal mucosa. From there, it communicates with an external device using radio signals to record the activity of gastric acid in the esophagus over a specified period of time. Unlike the conventional technique, which involves inserting a tube through the nose into the esophagus, the wireless capsule may be a more comfortable and tolerable alternative for patients, potentially improving adherence to the procedure. In some cases, patients may present chest pain after placement of the pH monitoring capsule, however there is little evidence about the etiology and management. We present the case of a woman with a clinical picture of gastroesophageal reflux, with pH monitoring capsule placement, which resulted in severe chest pain that required endoscopic capsule removal.